A facile and green route to terpene derived acrylate and methacrylate monomers and simple free radical polymerisation to yield new renewable polymers and coatings - Sainz, M.F.; Souto, J.A.; Regentova, D.; Johansson, M.K.G.; Timhagen, S.T.; Irvine, Derek J.; Buijsen, P.; Koning, C.E.; Stockman, R.A.; Howdle, Steven M. (Royal Society of Chemistry, 2016)
We present new acrylic monomers derived directly from abundant naturally available terpenes via a facile, green and catalytic approach. These monomers can be polymerised to create new polymers with a wide range of mechanical properties that positions them ideally for application across the commodity and specialty plastics landscape; from packaging, cosmetic and medical, through to composites and coatings. We demonstrate their utility through formation of novel renewable polymer coatings.